The Elitist Premises of Snouck Hurgronje's Association Fantasy - Dijk, Kees van (Studia Islamika, 2010)
Thee results of Snouck Hurgronje's initial experiment are now public knowledge. Achmad Djajadiningrat (1877-1943) was appointed Regent of Serang in 1901. He was 'elevated to this position after having enjoyed a thoroughly European upbringing,' Snouck Hurgronje lost no opportunity in writing to Van Heutsz in October 1905 (SH to VH 27-10-1905, Gobee and Adriaanse 1957-1965:538). In 1924 he became Regent of Batavia and, at the end of 1929, a Member of the Council of the Indies. On the recommendation of Snouck Hurgronje, Hoesein Djajadiningrat would go on to study Oriental languages in Leiden in 1905. In 1913 he became the firrst Indonesian to defend a PhD thesis (Djajadiningrat 1913). He passed with credit. In 1920 he was appointed Adjunct Advisor of Native A?airs. In 1924 he became a professor at the Law School in Batavia, and from 1935 to 1939 he was a Member of the Council of the Indies.DOI: 10.15408/sdi.v17i3.453